Analisis Korelasi Instagram @ui_makassar dan Penyebaran Informasi Akademik dan Non-Akademik - Ramdhaniah, Khusnul; Intizar, Raidah (Jurnal Komunikasi dan Organisasi (J-KO), 2025)
This study aims to analyze the relationship between the use of Instagram @ui_makassar and the dissemination of academic and non-academic information among students of Universitas Islam Makassar. Using descriptive quantitative method, data were collected through questionnaires from 365 respondents selected by simple random sampling. The simple linear regression test results showed a positive and significant correlation between the two variables, with a coefficient value of 0.717 and a significance of 0.000 (p < 0.05). This finding indicates that the more active the use of campus Instagram, the more effective the dissemination of information to students. This study confirms the importance of optimizing social media as a strategic communication channel in higher education and contributes to the study of digital communication in the academic environment.